The Influence of Religiosity and Hajj Waiting List on Customer Interest in Registering for Regular Hajj Quota (Case Study at Bank Muamalat Gorontalo Branch) - Gita Purnamasari; Niswatin Niswatin; Ronald S. Badu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of religiosity and the Hajj waiting list on customers' interest in registering for a regular Hajj quota at Bank Muamalat, Gorontalo Branch. A quantitative research method was employed, with primary data collected through a questionnaire distributed to Bank Muamalat customers. The sample consisted of 97 respondents. Data processing was conducted using SPSS version 16, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis. The results of the study showed that partially, religiosity had a positive and significant effect on customers' interest in registering for regular Hajj portions. Likewise, the Hajj waiting list variable has a positive and significant effect on the interest in registering for the regular Hajj portion. Simultaneously, both religiosity variables and the Hajj waiting list have a significant effect on customers' interest in registering for regular Hajj portions at Bank Muamalat Gorontalo Branch. These findings provide practical implications for Bank Muamalat Gorontalo Branch in particular, and Islamic banking in general to increase interest in Hajj registration through strengthening the value of religiosity and transparency of waiting list information in their marketing programs.